2017
DOI: 10.1007/s40820-017-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Driven Hydrogen Peroxide Production Using Polymer-Supported Carbon Dots as Heterogeneous Catalyst

Abstract: Safe, sustainable, and green production of hydrogen peroxide is an exciting proposition due to the role of hydrogen peroxide as a green oxidant and energy carrier for fuel cells. The current work reports the development of carbon dot-impregnated waterborne hyperbranched polyurethane as a heterogeneous photo-catalyst for solar-driven production of hydrogen peroxide. The results reveal that the carbon dots possess a suitable band-gap of 2.98 eV, which facilitates effective splitting of both water and ethanol und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…Carbon-based materials were also directly employed as photocatalysts for the production of H 2 O 2 without the addition of organic electron donors. [98] Under simulated sunlight irradiation, graphene oxide (GO) efficiently produced millimolar levels of H 2 O 2 .S imilar to GO,c arbon dots (CDs) can also serve as photocatalysts for the production of H 2 O 2 .G ogoi and Karak [99] employed water-soluble hyperbranched polyurethane (WPA) as as upport for acarbon dot photocatalyst, which was used for the solar-driven production Carbon materials can be incorporated with other non-TiO 2 semiconductors.T hakur et al [100] reported ah eterogeneous CdS-reduced graphene oxide (rGO) photocatalyst for the sustainable production of H 2 O 2 from H 2 Oa nd O 2 under sunlight. Thea mount of H 2 O 2 produced (128 mm)o ver the CdS/rGO hybrid photocatalyst was almost 5-times higher than that produced by CdS nanoparticles (27 mm)a fter irradiation with sunlight for 12 h. Similarly,J iang et al [101] tested aC dS/rGO composite for the generation of H 2 O 2 .…”
Section: Hybridization With Organic Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon-based materials were also directly employed as photocatalysts for the production of H 2 O 2 without the addition of organic electron donors. [98] Under simulated sunlight irradiation, graphene oxide (GO) efficiently produced millimolar levels of H 2 O 2 .S imilar to GO,c arbon dots (CDs) can also serve as photocatalysts for the production of H 2 O 2 .G ogoi and Karak [99] employed water-soluble hyperbranched polyurethane (WPA) as as upport for acarbon dot photocatalyst, which was used for the solar-driven production Carbon materials can be incorporated with other non-TiO 2 semiconductors.T hakur et al [100] reported ah eterogeneous CdS-reduced graphene oxide (rGO) photocatalyst for the sustainable production of H 2 O 2 from H 2 Oa nd O 2 under sunlight. Thea mount of H 2 O 2 produced (128 mm)o ver the CdS/rGO hybrid photocatalyst was almost 5-times higher than that produced by CdS nanoparticles (27 mm)a fter irradiation with sunlight for 12 h. Similarly,J iang et al [101] tested aC dS/rGO composite for the generation of H 2 O 2 .…”
Section: Hybridization With Organic Semiconductorsmentioning
confidence: 99%
“…Similar to GO, carbon dots (CDs) can also serve as photocatalysts for the production of H 2 O 2 . Gogoi and Karak employed water‐soluble hyperbranched polyurethane (WPA) as a support for a carbon dot photocatalyst, which was used for the solar‐driven production of H 2 O 2 from H 2 O, C 2 H 5 OH, and O 2 . The amount of H 2 O 2 produced on the C 2 H 5 OH/H 2 O mixtures solution reached about 70 μ m after 50 h of reaction.…”
Section: Advanced Photocatalysts For the Production Of H2o2mentioning
confidence: 99%
“…Tyagi et al [ 25 ] detected the catalytic performance of TiO 2 -water soluble carbon quantum dots (wsCQDs) was ~1.5 times more than that of TiO 2 . Gogoi et al [ 26 ] applied polymer-supported carbon dots to produce hydrogen peroxide. Another latent carbon material, carbon nanotubes (CNTs), are a kind of one-dimensional nanomaterial with high surface area and excellent conductivity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most popular combination to date has been citric acid as the carbon source, combined with nitrogen containing molecules, such as ethylenediamine or urea, while the most prominent formation route has been solvothermal processing. 60 For example, Peng et al used glucose and citric acid as the carbon sources and dopamine or 4,7,10-trioxa-1,13tridecanediamine as the nitrogen sources. Various combinations of these precursors were heated to form carbon dots with different photophysical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%